2004
DOI: 10.1088/0031-9155/49/23/012
|View full text |Cite
|
Sign up to set email alerts
|

A finite state model for respiratory motion analysis in image guided radiation therapy

Abstract: Effective image guided radiation treatment of a moving tumour requires adequate information on respiratory motion characteristics. For margin expansion, beam tracking and respiratory gating, the tumour motion must be quantified for pretreatment planning and monitored on-line. We propose a finite state model for respiratory motion analysis that captures our natural understanding of breathing stages. In this model, a regular breathing cycle is represented by three line segments, exhale, end-of-exhale and inhale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 14 publications
0
66
0
Order By: Relevance
“…Notably, the first few cycles of the VBF waveform that are used for the calibration had large breathing amplitudes that were not consistent with many of the other breathing cycles. In addition, both waveforms contain noise that is consistent with cardiac motion, (23) which may have adversely impacted the performance of prospective triggering. Figure 2 highlights a case study where improvements in image quality were observed when VBF was used.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the first few cycles of the VBF waveform that are used for the calibration had large breathing amplitudes that were not consistent with many of the other breathing cycles. In addition, both waveforms contain noise that is consistent with cardiac motion, (23) which may have adversely impacted the performance of prospective triggering. Figure 2 highlights a case study where improvements in image quality were observed when VBF was used.…”
Section: Resultsmentioning
confidence: 99%
“…Several models have been proposed to mimic tumour motions, see [6,9] and references therein. This paper proposes two stochastic linear models and a hybrid combination of them, which are suitable to use in both the Kalman filter and the IMM filter.…”
Section: Models and Filter Algortihmsmentioning
confidence: 99%
“…Since respiratory tumour trajectories may exhibit irregular motions as shown in [9], a single CV model or a single CA model may not be able to capture the dynamics in the complete trajectory. For this reason, a hybrid combination of the two models is proposed.…”
Section: Models and Filter Algortihmsmentioning
confidence: 99%
“…Our previous investigation developed a method of dynamic respiratory gating to compensate EOE baseline-shift 38 based on the finite state model (FSM) by Wu 39 which can identify the EOE phase of the tracked motion in real-time during treatment delivery. In this technical note, we will simulate an application of that method to evaluate the feasibility of using a dMLC to make the adjustments necessary for dynamic respiratory gating in a real-time tracking scenario with free breathing.…”
Section: Introductionmentioning
confidence: 99%